Natural iron isotopes influence on the neutron transport. (December 2017) - Schulc, Martin; Jánský, Bohumil; Harutyunyan, Davit; Novák, Evžen
Abstract: As an iron is the main structural component of nuclear power plants as well as future fusion power plants, the validation of neutron incident data libraries of iron is a must. Presented paper fits into ongoing validation activities and presents measuring neutron leakage spectra in the 0.1–1.0 MeV region from iron sphere of 100 cm in diameter by hydrogen proportional detectors. The experimental result is compared with ENDF/B-VII.1, JEFF-3.2 and CIELO nuclear data libraries. No library reasonably well describes whole region under study. Furthermore, elastic and inelastic XS sensitivity analysis for all iron isotopes was carried out. 54 Fe isotope elastic XS influence is comparable with 56 Fe XS influence up to 0.8 MeV. 57 Fe isotope elastic XS is significant in the region of 0.14–0.15 MeV. Additionally, there are large differences among libraries in both elastic and inelastic XS for 57 Fe. Furthermore, it was found that 58 Fe isotope XS has negligible influence on the results. As a neutron source, 252 Cf with initial emission rate of 9.53E8 n/s was used in this experiment. Highlights: Meaurement of neutron flux through iron sphere of diameter 100 cm in the energy range of 0.1–1.0 MeV. Effect of different data libraries on calculation result. Sensitivity analysis of 54 Fe, 56 Fe, 57 Fe and 58 Fe elastic and inelastic cross sections.